Qualidade da água balnear da comunidade de Ponta de Pedras – Santarém - Pará - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2018)
Bathing is an important instrument in the monitoring of water quality for the measurement of microbiological parameters. In this sense, the objective of this work was to evaluate the water quality for bathing purposes in Ponta de Pedras Community beach located in the city of Santarém - Pará. The methodology used consisted of surface water collection during two distinct periods of November / December 2015 and May / June 2016 - representing, respectively, low and upper waters of the Tapajós River, to analyze the parameters of total coliforms, thermotolerant and pH, investigating the possible correlations of rainfall rates with the densities of the parameters studied. However, the results were not significant to make spa water inadequate although there was a change in the category classification between the periods, being excellent in the low waters and very good in the high waters. This result can be attributed to the fact that Ponta de Pedras beach is still considered a natural environment, with minimal sources of pollution and low population density, which reflects positively on the quality of bathing water. Therefore, the monitoring of the water quality of the beach of Ponta de Pedras brings security to the bathers and can be object of public policies for the environmental issue in the municipality.
Keywords: Qualidade da Água; Balneabilidade; Precipitação; CNPQ:: ENGENHARIAS